PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK SARIAYU MARTHA TILAAR DI KONTER MARTHA TILAAR PASAR SWALAYAN ADA SEMARANG - Siti Rachma; Agus Hermani DS (Jurnal Ilmu Administrasi Bisnis, 2018)
Sariayu Martha Tilaar is the first cosmetic product brand manufactured by PT. Martina Berto Tbk. which is based on natural ingredients or spices of Indonesia's wealth and has once dominated the cosmetics industry market in Indonesia.However, in the midst of a very tight cosmetic product competition this cause Sariayu Martha Tilaar cosmetic products no longer dominate the cosmetics market in Indonesia. Sariayu cosmetics affordable price is not comparable with the quality of Sariayu products in the skin of the consumer face, causing consumers to buy only a little cosmetics, and with a nominal or total value of small shopping and seldom buy cosmetics Sariayu. The objective of this research is to analyze the influence of price and product quality to buying decision making of cosmetic product Sariayu Martha Tilaar in Martha Tilaar Counter, Ada Supermarket. This type of research is an explanatory research with a sample of 100 respondents Sariayu Martha Tilaar’s consumer.The sampling technique used is accidental sampling and purposive sampling with the criteria of respondents aged over 15 years, the respondent is female, and has been using Sariayu cosmetics at least 1 month of usage. Data collection using questionnaires with Likert measurement scale. Data analysis method used is validity test, reliability test, correlation coefficient (R), simple linear regression analysis, multiple linear regression analysis, coefficient of determination (R2), t test and F test using SPSS for Windows program. The results of this study conclude that Sariayu's price has a low (weak) influence on the purchase of Sariayu Martha Tilaar both partially and simultaneously. Meanwhile, the quality of Sariayu cosmetic products has no results from the purchase decision of Sariayu Martha Tilaar, either partially or simultaneously. Two variables have been tested in stages or together showing that the price variable (0.127) and product quality (-0.066) simultaneously have a relationship at a low level and very low on the variable purchase decision. The amount of the contribution from the price variable is greater than the contribution of the product quality variable, the coefficient of determination (R2) for the variable price of 12.4% and the product quality of only 2%. To improve purchasing decisions in relation to prices, the advice of researchers is that discounting should be done for consumers who pay in cash as well as often held and give product bonuses with attractive items, while the quality of the product is recommended. to be more durable, multiply products that are waterproof and improve product packaging to be more robust.